Patterns of Aortic Valve Replacement in Europe: Adoption by Age - Rudolph, Tanja; Appleby, Clare; Delgado, Victoria; Eltchaninoff, Helene; Gebhard, Catherine; Hengstenberg, Christian; Wojakowski, Wojtek; Petersen, Nathan; Kurucova, Jana; Bramlage, Peter; Bleiziffer, Sabine (Cardiology, 2023)
INTRODUCTION: The management of patients with severe aortic stenosis may differ according to patients' age. The aim of this analysis was to describe patterns of aortic valve replacement (AVR) use in European countries stratified by age. METHODS: Procedure volume data for AVR, including surgical aortic valve replacement (sAVR) and transcatheter aortic valve implantation (TAVI), for the years 2015-2020 were obtained from national databases for twelve European countries (Austria, the Czech Republic, Denmark, England, Finland, France, Germany, Norway, Poland, Spain, Sweden, and Switzerland). Procedure volumes were reported by patient age (<50 years, 5-year age groups between 50 and 85 years, and ≥85 years). Patients per million (PPM) population undergoing AVR each year were calculated using population estimates from Eurostat. RESULTS: AVR PPM varied widely between countries, from 508 PPM in Germany to 174 PPM in Poland in 2020. TAVI rates ranged from 61% in Switzerland and Finland to 25% in Poland. AVR PPM increased with age to a peak at 80-84 years, after which it decreased again. AVR procedures increased from 2015 to 2019 at an average annual rate of 3.9%. AVR increased more substantially in people aged ≥80 years than in younger age groups; these older age groups accounted for 30% of all AVR procedures in 2015 and 35% in 2019. TAVI accounted for an increasing proportion of all AVR procedures as patient age increased; an overall average of 96% of males and 98% of females aged ≥85 years received TAVI as the treatment modality, although adoption of TAVI differed between countries. CONCLUSIONS: There is considerable variation in the rates of AVR use and the adoption of TAVI versus sAVR between European countries. The use of TAVI has increased in recent years, particularly for older patients.
Keywords: senioři; Age; Aortic Valve; Europe; výsledek terapie; Evropa; mužské pohlaví; Transcatheter aortic valve implantation; Transcatheter Aortic Valve Replacement; Aortic valve replacement; transkatetrální implantace aortální chlopně; aortální chlopeň; Aortic Valve Stenosis; chirurgická náhrada chlopně; Heart Valve Prosthesis Implantation; ženské pohlaví; Humans; rizikové faktory; aortální stenóza; Female; Aged; Risk Factors; Treatment Outcome; lidé; Male